2022
DOI: 10.1111/ans.17667
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery on patients with COVID‐19: a systematic review and meta‐analysis

Abstract: Introduction:The COVID-19 pandemic has had a significant impact on global surgery. In particular, deleterious effects of SARS-CoV-2 infection on the heart and cardiovascular system have been described. To inform surgical patients, we performed a systematic review and meta-analysis aiming to characterize outcomes of COVID-19 positive patients undergoing cardiac surgery. Methods: The study protocol was registered with PROSPERO (CRD42021228533) and conformed with PRISMA 2020 and MOOSE guidelines. PubMed, Ovid MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Inconclusive results have been reported by other studies that have observed either increases or no changes in IHM in relation to such interventions before and during the COVID-19 pandemic [27][28][29][30][31]. In a recent systematic review and meta-analysis, it was reported that COVID-19 patients undergoing cardiac surgery have poor outcomes [32]. These results were confirmed in our investigation where IHM was much higher among patients with COVID-19 infection (Tables S3 and S4).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inconclusive results have been reported by other studies that have observed either increases or no changes in IHM in relation to such interventions before and during the COVID-19 pandemic [27][28][29][30][31]. In a recent systematic review and meta-analysis, it was reported that COVID-19 patients undergoing cardiac surgery have poor outcomes [32]. These results were confirmed in our investigation where IHM was much higher among patients with COVID-19 infection (Tables S3 and S4).…”
Section: Discussionsupporting
confidence: 90%
“…Various studies have indicated that SARS-CoV-2 infection acts on endothelial cells not only in the lungs but also in blood vessels and the heart, causing deterioration processes, such as inflammation and oxidative stress, and numerous cardiovascular complications. In addition, new data shows that even asymptomatic patients, not just patients with symptoms, can experience these complications immediately after illness, in the next 30 days, and even after a year [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…36 For surgical systems worldwide, preoperative screening, triage, and intraoperative practice has been affected by the risk of COVID-19 transmission in the community. [37][38][39][40] Modern technology allows healthcare to be delivered and consumed through the internet, whilst also limiting physical movement of persons and in effect, lowering the density per area of people at healthcare centers. The combined effect has been to reduce risks of COVID-19 transmission to patients and healthcare staff.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in less face‐to‐face medical care and provides a challenge in delivering healthcare 36 . For surgical systems worldwide, preoperative screening, triage, and intraoperative practice has been affected by the risk of COVID‐19 transmission in the community 37–40 . Modern technology allows healthcare to be delivered and consumed through the internet, whilst also limiting physical movement of persons and in effect, lowering the density per area of people at healthcare centers.…”
Section: Discussionmentioning
confidence: 99%
“…Open heart surgery in patients with coronavirus disease 2019 (COVID-19) infection creates various problems, such as coagulopathy, hypoxia, difficulty weaning, and susceptibility to secondary bacterial infections. In addition to surgical trauma, impaired extracorporeal circulation and impaired myocardial and pulmonary reserve can lead to immunosuppression and coagulopathy, which further complicate the management of these patients [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%